Data, Metrics, and Monitoring in CGIAR - Strategic Study - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2014)
This document contains the final report of the Panel together with the ISPC commentary. The Panel Report presents an analysis of the current activities within CGIAR concerning data, metrics, and indicators, and offers a series of recommendations to address the key issues and challenges identified.